A multicenter study to investigate the positive rate of SARS-CoV-2 in middle ear and mastoid specimens from otologic surgery patients. Issue 2 (April 2023) - Yamazaki, Hiroshi; Yamamoto, Norio; Sonoyama, Toru; Maruoka, Hayato; Nasu, Seiko; Makino, Akiko; Tomonaga, Keizo; Shigemoto, Norifumi; Ohge, Hiroki; Fujiwara, Keizo; Shinohara, Shogo; Takeno, Sachio; et al.
Abstract: Objective: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a novel coronavirus, causes coronavirus disease 2019 (COVID-19). Otologic surgeries with drilling by powered instruments induce significant aerosols, which may induce SARS-CoV-2 transmission to medical staff if SARS-CoV-2 exists in the middle ear and mastoid cavity. During a COVID-19 pandemic, therefore, confirming a negative COVID-19 test prior to otologic surgery is recommended. However, previous coronavirus studies demonstrated that coronavirus was detected in the middle ear in some patients even though the polymerase chain reaction (PCR) test using their nasopharyngeal swab was negative. This study aimed to elucidate the probability of a positive SARS-CoV-2 PCR test in the middle ear or mastoid specimens from otologic surgery patients in whom SARS-CoV-2 was not detected by preoperative PCR test using a nasopharyngeal swab. Methods: We conducted a prospective, multicenter clinical study. Between April 2020 and December 2021, during the COVID-19 pandemic, 251 ears of the 228 participants who underwent otologic surgery were included in this study. All participants had no symptoms suggesting COVID-19 or close contact with a confirmed COVID-19 patient two weeks prior to the surgery. They were also negative in the SARS-CoV-2 PCR tests using a nasopharyngeal swab before surgery. We collected mucosa, granulation, bone dust with mucosa or fluid from the middle ear or mastoid for the SARS-CoV-2 PCR tests during each otologic surgery. Results: The median age of the participants at surgery was 31.5 years old. Mastoidectomy using a powered instrument was conducted in 180 of 251 otologic surgeries (71.8%). According to intraoperative findings, active inflammation in the middle ear or mastoid cavities was evident in 20 otologic surgeries (8.0%), while minor inflammation was observed in 77 (30.7%). All SARS-CoV-2 PCR tests of otologic specimens showed a negative result. No patient suffered from COVID-19 within two months after otologic surgery. Furthermore, no hospital-acquired infections associated with otologic surgery occurred in our institutions Conclusions: Our results showed that PCR testing did not detect SARS-CoV-2 in middle ear and mastoid specimens, suggesting that the risk of transmission of SARS-CoV-2 is not high in otologic surgeries even using powered instruments when both clinical and laboratory tests are confirmed to be negative for COVID-19.